The Form of American Romance - Dryden, Edgar (Johns Hopkins University Press, 2019)
Originally published in 1988. Edgar Dryden challenges recent criticism that has tended to discredit-or at least devalue-the importance of "romance" as a thematic and generic category of American fiction. In The Form of American Romance, he examines its evolution and meaning through readings of five exemplary texts: Hawthorne's Marble Faun, Melville's Pierre, James's Portrait of a Lady, Faulkner's Absalom, Absalom!, and Barth's Letters. Each of these novels treats the problems of reading and writing in a self-referential way that reflects on the questions they dramatize, and Dryden has chosen each with the others in mind. Taken together, they chart a line of development with representative examples of what literary history calls romanticism, realism, modernism, and postmodernism, and thus they suggest a certain story about the continuity of the American novel.